EDUKASI PENERAPAN PHBS MENGGOSOK GIGI DAN CUCI TANGAN DENGAN BENAR PADA SISWA KELAS V MI MA’ARIF NU BANTERAN - Putri , Yurice Kusuma; Rahmawati, Helda Budi; Parasasri , Ayu Rahma Kusuma; Audina, Rina; Kusumawardani, Lita Heni (Jurnal Pengabdian kepada Masyarakat (NADIMAS), 2023)
Community nursing is aimed at maintaining health, providing assistance through nursing interventions in helping individuals, families, groups and communities to overcome the health problems they face. Based on 2018 Riskesdas data, as many as 67.3% of children aged 5-9 years and 55.6% of children aged 10-14 years experienced dental and mouth problems. Based on the results of a study conducted on class V students at MI Ma'arif NU Banteran, it was found that 67.6% of students had problems with sore, cavities or blackened teeth. During the study, it was found that 4 out of 68 students only brushed their teeth once a day. The aim of this community service is to provide community nursing care in the school community in Banteran Village, Sumbang District in an effort to improve the health status of school residents. The activities were carried out with education and demonstrations related to PHBS which were held at MI Ma'arif NU Banteran on Monday, October 16 2023. The target of the activities was grade 5 students consisting of 68 students. This target was chosen based on the results of the survey and screening that had been carried out. Before carrying out the activity, students are given a pretest sheet to determine student understanding. The activity continued by providing information and skills through lecture and demonstration methods including material on how to brush your teeth properly and correctly and how to wash your hands in 6 steps. The media used are power points and dental phantoms. After the activity, an evaluation is carried out by providing a posttest sheet. Based on the results of data analysis, it shows that there was an increase in the average pretest score of 83.1, increasing to 89.9 during the posttest activity. Educational activities and 6-step PHBS demonstrations of toothbrushing and hand washing significantly influence students' knowledge and skills regarding PHBS behavior.